1993
DOI: 10.1037/0022-3514.64.6.906
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the experiences of envy and jealousy.

Abstract: This article describes the nature and significance of the distinction between the emotions of envy and jealousy and reports 2 experiments that empirically investigated it. In Experiment 1, Ss recalled a personal experience of either envy or jealousy. In Experiment 2, Ss read 1 of a set of stories in which circumstances producing envy and jealousy were manipulated independently in a factorial design. Both experiments introduced new methodologies to enhance their sensitivity, and both revealed qualitative differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
702
1
55

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 639 publications
(780 citation statements)
references
References 28 publications
22
702
1
55
Order By: Relevance
“…Although Parrott and Smith's (1993) work demonstrated that the experiences of envy and jealousy are distinguishable, with distinctive features that compose orthogonal components, this does not in itself show that they represent discrete categories. For example, neuroticism and extraversion are distinct, orthogonal personality dimensions, but there is no evidence that there are discrete categories of neurotics and extraverts (Eysenck, 1967).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although Parrott and Smith's (1993) work demonstrated that the experiences of envy and jealousy are distinguishable, with distinctive features that compose orthogonal components, this does not in itself show that they represent discrete categories. For example, neuroticism and extraversion are distinct, orthogonal personality dimensions, but there is no evidence that there are discrete categories of neurotics and extraverts (Eysenck, 1967).…”
mentioning
confidence: 99%
“…As manifest variation may be continuous whether the latent situation is continuous or discontinuous, specialized methodologies are required to test between these alternatives. The present study attempted to perform such tests on the manifest differences between envy and jealousy demonstrated by Parrott and Smith (1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is, however, a fine distinction between the two in that the former involves two people and corresponds to the manifestation of feelings when a person wishes to gain an advantage over another, while the latter involves three people and refers to the feelings aroused when a person fears losing a special relationship with a rival (Epstein, 2006). These terms, however, are often mistaken due to the semantic ambiguity regarding the way in which the word "jealousy" is used in English and because of the frequent occurrence of these two emotions, either simultaneously or separately (Parrott & Smith, 1993).…”
Section: Jéssica Bruna Santana Silva Universidade Federal Da Paraíbamentioning
confidence: 99%
“…Emotions have social functions [6], and society has an influence on our emotions [7]. Emotions also play a role in our perception of reality down to the perception of our own body generated signals such as pain.…”
Section: Introductionmentioning
confidence: 99%